Complex criminal cases - Orsi, Omar G.; Rodríguez-García, Nicolás (EUNOMÍA. Revista en Cultura de la Legalidad, 2025)
The criminal procedure does not show the same efficiency in complex criminal cases as in simple ones. One of the factors that may explain this low efficiency is the lack of models and tools suitable for processing massive data. To take advantage of the availability of information in the digital era, it is necessary for criminal justice systems to complement the traditional hermeneutic model and investigation methodology with contributions from other sciences.